Challenges and Responses to Islamic Education in the Technology Era 4.0 - Zubairi Zubairi (AL-ISHLAH: Jurnal Pendidikan, 2023)
Islamic religious education as a process of growing and developing the intellectual, spiritual, physical, social, ethical, aesthetic and moral (moral) potential of students. So that it can grow and be nurtured optimally, by nurturing, nurturing, caring for, repairing and developing it in a planned, systematic, methodological and sustainable manner.The Industrial Revolution 4.0, which is full of super-fast technology, will bring significant changes, one of which is the education system in Indonesia. Changes in the education system have an impact on the role of teachers as educators. In facing the Revolution 4.0 era, the world of education plays an important role in improving the quality of human resources. Students are expected to have 21st century life skills known as 4C, namely creativity, critical thinking, communication, and collaboration. Therefore there are three things that educators must take advantage of in the era of society 5.0, including: the Internet of things in the world of Education (IoT), Virtual/Augmented reality in the world of education, and the use of Artificial Intelligence (AI) to find out and identify learning needs that are needed by students